ESTIMATED DAILY INTAKE AND EXPOSURE OF SODIUM BENZOATE AND POTASSIUM SORBATE THROUGH FOOD PRODUCTS IN SCHOOL CHILDREN OF TIRUPATI, INDIA - Reddy, M Vivek; Aruna, G; Parameswari, S Angala; Banu, B Haseena; Reddy, P Jayachandra (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Objective: According to Food Safety and Standards Authority of India (FSSAI) the preservatives, sodium benzoate and potassium sorbate belong to permitted class II preservatives. The aim of this study is to determine the concentration levels of these preservatives in food products that are consumed by school children and to assess the chronic dietary exposure by conducting the Total Diet Study (TDS). Methods: The quantitative determination was carried out by UV spectrophotometer. The absorbance for sodium benzoate and potassium sorbate were measured at 228 and 250 nm respectively. The 24-hour diet recall method was used to estimate the amount of food ate in last 24 hours. For estimation of preservative exposure dietary modelling techniques were utilized which combine the amount of preservative concentration present in that food with the amount of food consumed. Then the dietary exposure was assessed by considering the Acceptable Daily Intake (ADI). Results: The results include chemical concentration levels of the foods analyzed as well as estimated dietary exposures and contributions to the exposure from different foods. The obtained mean concentration of sodium benzoate was found to be425 ppm for sauces, 161 ppm for pickles and 80 ppm for soft drinks. Potassium sorbate was found to be 130 ppm for fruit juices,302 ppm for jellies and 380 ppm for jams. The highest mean dietary exposure for both the preservatives was observed in children of 2-7 years age group, the percentage exposure of sodium benzoate was 33% of the ADI and potassium sorbate was 17 % of the ADI. Conclusion: This study can enlighten the public on the consumption of preservative containing food products within the limit and encourages to eating fresh preservative free foods. Â 